Density Functional Theory Calculation May Confirm Arsenic–Thiol Adhesion as the Primary Mechanism of Arsenical Toxicity - Tsai, Meng-Han; Lin, Ying-Ting (ACS omega, 2024)
Previously, it was believed that methylation was the body’s primary method to detoxify inorganic arsenic. However, recent research has shown that the metabolized intermediate known as MMAIII is more toxic than arsenite and arsenate, contradicting a previous understanding. Another important question arises: is arsenical toxicity truly caused by arsenic binding to proteins through arsenic thiol adhesion? Based on the toxicity order of the experiment, with MMAIII being the most toxic, followed by arsenite, arsenate, DMAV, and MMAV, density functional theory (DFT) calculations can provide a straightforward assessment of this issue. Our practice captures all the transition states associated with a specific imaginary-frequency vibration mode, including proton transfer and simultaneous departure of leaving group. We have obtained the energy barriers for five arsenicals reacting with thiol, alcohol, and amine separately. In addition to energetic favorability, the following are the energy barriers for arsenic’s reaction with thiol ranked from low to high: MMAIII (25.4 kcal/mol), arsenite (27.7 kcal/mol), arsenate (32.8 kcal/mol), DMAV (36.2 kcal/mol), and MMAV (38.3 kcal/mol). Results show that the toxicity of arsenicals is mainly caused by their reaction with thiol rather than with alcohol or amine, as supported by the trend of decreasing toxicity and increasing energy barriers. Thus, this DFT calculation may confirm the paradigm that arsenic–thiol adhesion is the primary cause of arsenic toxicity in the body.